Geodiversidade das unidade de paisagem da Bacia Hidrográfica do Rio Piauí - Sergipe - Santana, Bruna Leidiane Pereira (2023)
Geodiversity is established as the plurality of abiotic components that constitute landscapes and terrestrial environments together with their processes of origin, dynamics, and interaction with biodiversity. Lithology, relief, pedological coverage, and water resources constitute the structure for the existence and maintenance of fauna, flora, and human production. In evidence, the thesis aimed to analyze the Piauí River hydrographic basin with an emphasis on its landscape units, based on the integration of methodologies that would enable its inventory, quantification, and ecosystem assessment. In principle, the compartmentalization of the landscape resulted in the units of the Rio Real Tableland subdivided into Summit Structural Surface, Karst Flattening Surface, Dissected Surface in Hills, Preserved Flattened Surface, Hills and Low Hills, Pediplaned Surface and Low Mountains and Hills and Coastal Tableland with the subunits Convex Top Hills and Spikes, Subhorizontal Surface and Elongated Hills and Spikes. To carry out the thesis, the methodology allowed identification that the highest rates of geological, pedological, and geomorphological diversity are manifested in the subunits of Tabuleiro do Rio Real, as well as the inventoried geosites, Serra do Cruzeiro, Serra da Pedra Branca, Serra dos Palmares , Source of the Piauí river and Toca da Raposa Cave. For ecosystem services, regulation, support, provision, and knowledge services can be evaluated. The criterion highlights the support service with high relevance in Coastal Tablelands, through goods and processes of soil, platform, construction materials, and water resources. The methodology used presented significant results on the diversity of the basin, making it possible to infer that the different environments that make up the landscape of the Piauí River basin have natural potential for valuing geodiversity in scientific, educational, and geotouristic aspects. From another perspective, it is noticeable that the dissemination of conservation and dissemination actions occurs on a punctual basis, despite their significance.